MOLD PROPERTIES OF INDONESIA NATURE SAND AS GREEN SAND - Hendronursito, Yusup; Amin, Muhammad; Isnugroho, Kusno; Birawidha, David Candra (Deputi TIRBR-BPPT, 2019)
The mould properties of Juwono sand, were investigated. The samples were subjected to various physical and mechanical test. These include permeability, green compression strength, and chemical composition by XRF/ XRD analysis. Green shear strength, grain shape, water content, and clay content were also carried out on the samples. Juwono sand casting containing 32.76% clay and category in grade 212/75 of fine sub grades were found to posses adequate permeability, good strength and refractoriness suitable for casting of both ferrous and non ferrous alloys.